Limits on the effective quark radius from inclusive ep scattering at HERA - Abramowicz, Halina; Lisovyi, Mykhailo (Physics letters, 2016)
The high-precision HERA data allows searches up to TeV scales for beyond the Standard Model contributions to electron-quark scattering. Combined measurements of the inclusive deep inelastic cross sections in neutral and charged current ep scattering corresponding to a luminosity of around 1 fb−1 have been used in this analysis. A new approach to the beyond the Standard Model analysis of the inclusive ep data is presented; simultaneous fits of parton distribution functions together with contributions of “new physics” processes were performed. Results are presented considering a finite radius of quarks within the quark form-factor model. The resulting 95% C.L. upper limit on the effective quark radius is 0.43⋅10−16 cm.